Evaluation of Heavy Metals and Total Hydrocarbon Concentration in the Qua Iboe River Estuary, Akwa Ibom State, Nigeria - Eni, D. Imoke; Arikpo, I. Abam; Oko, Peter Ereh (Mediterranean Journal of Social Sciences, 2021)
The research assessed the concentration level of heavy metals and total hydrocarbon in Qua Iboe River Estuary of Akwa Ibom State, Nigeria during the months of April, May and June. The experimental research design was adopted and a total of 72 water samples were collected on weekly basis from ST1, ST2 and ST3 during high and low tides in thoroughly-rinsed 1-litre plastic containers to avoid adulteration of the samples. Samples were analyzed in-situ and in the laboratory using standard methods. The results of the concentrations of the sampled parameters during high tide included: Cr (0.003-0.21mgl-1), Fe (0.123-0.511mgl-1); Mn (0.018-0.66mgl-1), Pb (0.105-0.603mgl-1), Mg (0.42-0.623mgl-1), Cu (0.00-0.32mgl-1) and THC (0.12-0.88mgl-1)while the low tide concentrations showed: Cr (0.001-0.061mgl-1), Fe (0.56-4.11mgl-1), Mn (0.002-0.13mgl-1), Pb (0.011-0.211mgl-1), Mg (0.108-1.342mgl-1), Cu (0.011-0.076mgl-1) and THC (0.23-0.80mgl-1). The concentrations of Hg and As were negligible throughout the study. Analysis revealed that THC varied significantly across the sampled stations (ANOVA, P <0.001). Pollution Index, PI <1 for Ni, Mn, Na, Hg, As, Mg and Cu, implied that there was no pollution in the estuary. Fe showed that the estuary was slightly polluted with PI 1-2; Cr, V and THC recorded PI 2-3 signifying that the water was moderately polluted; PI >5 for Pb revealed that the estuary was seriously polluted with lead. The oil spills by ExxonMobil’s offshore platforms in the area, the heinous practices of waste dumping along the coast have resulted in the high THC and heavy metals concentrations found in the water samples. Hence, the water in Qua Iboe River Estuary is polluted and not safe for personal or domestic uses. The study recommended that Exxon Mobil and other oil companies in Nigeria should adhere strictly to international best practices in oil exploration/exploitation, environmental conservation, maintenance of equipment and safety of their infrastructure should be their priority. Prompt actions should be taken towards clean-up exercises in case of oil spill incidents in the area and proper, modern sewage and solid wastes disposal mechanism should be put in place by the host communities. Received: 31 January 2021 / Accepted: 27 February 2021 / Published: 7 March 2021